STUDI KELAYAKAN INSTALASI LISTRIK PADA GEDUNG GELANGGANG OLAHRAGA MAMPIS RUNGAN KABUPATEN SUMBAWA SESUAI PERSYARATAN UMUM INSTALASI LISTRIK 2011 - Andhika Diva Dwi Sandi; Muhammad Hidayatullah; Indra Darmawan; Ahmad Jaya (Jurnal Altron, 2026)
Proses Electrical installations are systems that provide electrical power to meet human needs in everyday life. This involves distributing electric power from the distribution substations of electricity service providers to load points. In the distribution of electrical energy, general requirements for electrical installations are enforced to ensure safety because they ensure human safety and protect property from electrical hazards. Failure to comply with electrical installation regulations and standards can cause the risk of accidents, fires and other serious dangers for building occupants. These problems need to be addressed. carry out feasibility tests on electrical installations that comply with the general requirements for electrical installations in 2011 to ensure safety, reliability and quality of electrical installations. This research aims to determine the feasibility of electrical installations for the Mampis Rungan sports arena building in Sumbawa Regency. This research uses a qualitative method of observation which includes testing, Observations and interviews This research does not involve statistical analysis but focuses more on data collection, analysis and interpretation. Based on the results of inspection and testing data which have been in accordance with PUIL 2011, the Mamp?s Rungan Sports Arena Electrical Installation can be declared unfit. The unfitness factor is caused by The electrical installation system from the panel to the load point does not meet PUIL 2011 standards which include the color of the cables on the panel, and the cables that go to the load point as well as installation safety measures such as the absence of lasdops